Fugas, afetos e instabilidade: narrativas e reflexões sobre deslocamentos e migração no devir da formação docente - Lima, Angélica Rodrigues (2019)
This is a narrative survey with emphasis on autobiographical methodology aiming at discussing and analyzing experiences of displacement and migration in processes of educational formation. We investigated the paths, stories and experiences of six students in the program of Visual Arts degree who had experienced migration seeking to have their undergraduate degree on the Faculdade de Artes Visuais (FAV – School of Visual Arts) of the Federal University of Goiás (UFG). This thesis structured in four chapters. The first chapter contains theoretical reference on the areas of education, arts, and visual culture to suport a discussion of fundamental two axes regarding the research development. The first axis focuses on the life stories and the construction of narratives using the autobiographical approach, while the second axis brings a discussion on experiences of displacement and migration in processes of educational formation. The chapter also presents conceptions on the qualitative methodology and focus group to introduce the procedures used to carry out the field survey in order to produce data. We also highlight the sociological context of the participants, along with field remarks, the meetings and interviews, actions as well as focus group events. The second chapter reveals fragments of my own life story and educational formation, whichare constantly linked to one another through narratives throughout the chapter aiming at tracing some experiences which had led me to walk through/and/with the theme of geographical displacement, encompassing from personal childhood trajectories to daily and academic experiences. The third chapter analyzes the data produced from the field work by putting in perspective the interpretation of both individual and collective narratives created by the focus group considering the fourth categories that I regard as relevant in the investigation process. The first one is the “narrative environment”, (place/ research field), which leads me to wonder: how do life stories gain force to discuss the research theme? The second category originates from the “processes of thinking narratives with images” in which I address and reflect on the importance of images to move life stories, their decision-making, deconstructions, and reconstructions by the focus group. The third category, in turn, “visual narratives and life stories”, helped me to think the displacements, migratory movements, and educational formation regarding a dialogue with the principles of visual culture. And the fourth category, which seeks to reflect on the collaborative work foreseeing to deepen the discussion about teacher education. The fourth chapter synthetizes the main results of the survey by highlighting the processes of investigation taken over by constant transformations of view/time/space/formation. The events, visualities and insurgencies that occurred in the field work helped to identify learning possibilities through life stories and personal narratives. In addition, I point out the range of the investigation by projecting possible developments for further studies.